1987
DOI: 10.1007/bf03392818
|View full text |Cite
|
Sign up to set email alerts
|

Rule-following and human operant responding: Conceptual and methodological considerations

Abstract: A conceptual analysis of rule-govemed behavior, emphasizing pliance and tracking as functional classes of rule-following, is provided and related to previous methodological strategies in human operant research. A novel strategy, which utilizes a microcomputer to reinforce correspondences between subject guesses and responding, is proposed for the study of rule-following. Results from a preliminary demonstration of the procedures are reported briefly, and possible applications to the further analysis of rule-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Four studies stated that their research goal was to examine the effects of pliance (i.e., Berry et al, 1992, along with three studies reported in Donadeli & Strapasson, 2015). One study reported that it intended to investigate whether empirical evidence existed for the concept of tracking (i.e., Zettle & Young, 1987). Two studies were identified that stated that their primary focus was to examine formative augmenting (i.e., two studies in Whelan & Barnes-Holmes, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies stated that their research goal was to examine the effects of pliance (i.e., Berry et al, 1992, along with three studies reported in Donadeli & Strapasson, 2015). One study reported that it intended to investigate whether empirical evidence existed for the concept of tracking (i.e., Zettle & Young, 1987). Two studies were identified that stated that their primary focus was to examine formative augmenting (i.e., two studies in Whelan & Barnes-Holmes, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…This finding has stimulated several areas of research evaluating variables and methodological manipulations that affect the relative degree of rule following. Research indicates rule-governed behavior may be modulated by several variables, including completeness of the rules (e.g., Podlesnik & Chase, 2006), feedback on the performance of a task (Baron et al, 1969), the function-altering phrasing of the rules (e.g., Schlinger & Blakely, 1987;Zettle & Young, 1987), changes in the contingencies and accuracy of the rules (e.g., Baumann, Abreu-Rodrigues, & da Silva Souza, 2009;Fox & Pietras, 2013;Hackenberg & Joker, 1994), and the degree of discrepancy between stated rules or instructions 1 and actual reinforcement contingencies (e.g., DeGrandpre & Buskist, 1991;Galizio, 1979). For example, results from Galizio suggest that responding in an avoidance paradigm will follow the instruction when the instruction is accurate; however, responding may deviate when instructions are inaccurate and individuals contact the actual contingency in the form of the loss of points.…”
mentioning
confidence: 99%
“…First, the importance of using a procedure that minimizes social control as much as possible has been highlighted by different authors (Critchfield, Tucker, & Vuchinich, 1998;Gomez & Luciano, 2000;Zettle & Young, 1987) and is supported by data indicating that social contingencies have a real impact on the performances of subjects and on verbal statements (Barrett, Deitz, Gaydos, & Quinn , 1987;Williams, 1985). The use of a PIN for subjects, hiding the tape recorder and cables, and subjects working alone on the task, were some of the measures taken for that purpose.…”
Section: Discussionmentioning
confidence: 99%